PEMBAGIAN TUGAS, IKLIM KERJA, TAMBAHAN PENGHASILAN PEGAWAI DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI: (Kasus Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Tenggara) - Akbar Wahbi; Jamal Bake; Malik; Syamsul Alam (Journal Publicuho, 2023)
The purpose of this study was to find out and analyze the effect of division of tasks, work climate and additional employee income on employee performance. The research uses a quantitative approach, involving 37 respondents taken randomly from 58 employees who make up the study population. The questionnaire uses a Likert scale, (1-5), data analysis uses a multiple regression model with SPSS version 26.0 facilities and hypothesis testing uses an alpha of 0.05. Research results 1) The division of tasks, work climate and provision of TPP have a significant effect on employee performance. The three variables show a significant positive effect on employee performance, meaning that the better the division of tasks, the conducive work climate and the fair provision of TPP, the higher the employee performance; 2) The results of the partial test also prove that the division of tasks has a significant effect on employee performance, the effect is positive and significant, meaning that a proportional division of tasks increases employee performance; 3) Work climate has a significant and positive effect on employee performance, meaning that the more conducive the work climate is, the higher the employee performance in carrying out their duties; 4) Provision of TPP has a significant and positive effect on employee performance, meaning that the fairer the TPP is, the employee's performance will also increase.